Review of Librarian Experiences in Performing Work Adaptation at the Archives and Library Service of Kendal Regency - Alvin Mighfar Bahri; Roro Isyawati Permata Ganggi (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: The librarian is an evolving profession, which requires librarians to engage in lifelong learning, in order to adapt to the changes that occur in a dynamic library environment. Good adaptability is needed by librarians to be able to maintain optimal performance.Objective: The purpose of this study is to discuss the adaptability of the performance of librarians at the Kendal Regency Archives and Library Service.Methods: This research uses qualitative research methods with a case study approach. Data collection techniques were carried out by means of observation, interviews and documentation. Selection of informants in this study using purposive sampling technique. The informants in this study amounted to 2 (two) librarians from the Kendal Regency Archives and Library Office. Data analysis was carried out with several stages proposed by Miles and Huberman, namely, data reduction, data presentation and drawing conclusions.Results: The results showed that librarians at the Kendal Regency Archives and Library Office have adaptability and basic skills that are useful in adapting to changes to maintain optimal performance. The basic skills possessed by librarians at the Kendal Regency Archives and Library Office include conceptual skills, technical skills, interpersonal relationship skills and are complemented by the ability to adapt in the form of passion, time management, networking, and hummility.Conclusion: Adaptation principles such as a never-give-up attitude, effective time management, and the ability to communicate and collaborate effectively are efforts by librarians to respond to these changes.